Spinesuit device a low cost, easy to wear and customizable semirigid brace for kids aged 10 to 18 years with biopathic scoliosis - Duran, Perry Irish Hufana
For more than 150,000 Filipinos, there occurs an abnormal side-to-side (lateral) curve in the spinal column, which people refer to as scoliosis. Eighty percent of these cases is idiopathic and is commonly found in young adults around the onset of puberty. To stop the progression of scoliosis, a patient is to wear a brace, usually, for 23 hours every day in a year or more. This is a real challenge for the wearer because of the physical and social discomforts that one may get in wearing a brace, and also a challenge for doctors to see to it that patients will comply. Thus, a study to improve the design of the traditional rigid brace is made to ensure the compliance of the patient in wearing scoliosis brace and to gain a better outcome of scoliosis treatment by addressing the patient's needs and preferences. Spinesuit Device - a low cost, easy to wear and customizable semirigid brace - is designed to make the brace-wearing experience lighter and fun!